Allosteric Coupling between the Intracellular Coupling Helix 4 and Regulatory Sites of the First Nucleotide-binding Domain of CFTR - Dawson, Jennifer E.; Farber, Patrick J.; Forman-Kay, Julie D. (PLOS ONE, 2013)
Cystic fibrosis is caused by mutations in CFTR (cystic fibrosis transmembrane conductance regulator), leading to folding and processing defects and to chloride channel gating misfunction. CFTR is regulated by ATP binding to its cytoplasmic nucleotide-binding domains, NBD1 and NBD2, and by phosphorylation of the NBD1 regulatory insert (RI) and the regulatory extension (RE)/R region. These regulatory effects are transmitted to the rest of the channel via NBD interactions with intracellular domain coupling helices (CL), particularly CL4. Using a sensitive method for detecting inter-residue correlations between chemical shift changes in NMR spectra, an allosteric network was revealed within NBD1, with a construct lacking RI. The CL4-binding site couples to the RI-deletion site and the C-terminal residues of NBD1 that precede the R region in full-length CFTR. Titration of CL4 peptide into NBD1 perturbs the conformational ensemble in these sites with similar titration patterns observed in F508del, the major CF-causing mutant, and in suppressor mutants F494N, V510D and Q637R NBD1, as well as in a CL4-NBD1 fusion construct. Reciprocally, the C-terminal mutation, Q637R, perturbs dynamics in these three sites. This allosteric network suggests a mechanism synthesizing diverse regulatory NBD1 interactions and provides biophysical evidence for the allosteric coupling required for CFTR function.